Efektivitas Project Based Learning dalam Meningkatkan Keterampilan Menganyam bagi Anak Tunagrahita Ringan (Pre-Exsperiment di Kelas X SLB Ummi Khaira Pasaman Barat) - Yendika Arya Fajri; Jon Effendi (Universitas Negeri Padang, 2023)
This study aims to show whether project based learning is effective for improving weaving skills for students with mild intellectual disabilities. The type and design used in this study is an experiment that can be used in research, namely Pre-Experiment. The type of experimental design used is a one group pre test and post test design. . From the results of the Wilcoxon sign rank test, the results of this study prove that the Project Based Learning method is effective in improving vocational skills in making woven palm oil sticks for mild mentally retarded children in class X at SLB Ummi Khaira, West Pasaman. By using the Project Based Learning method, you can complete a project that is carried out together or in a group so that the project carried out can run well.